The Influence Of The Korean Wave, Hedonistic Lifestyle, And Brand Image On Purchase Decision Of Samsung Products With Customer Relationship Management As A Moderating Variable (Case Study: Samsung Gadget Consumers in DKI Jakarta) - Lisa Azizah Subagiyo (Publikasi Indonesia, 2025)
This study examines the influence of the Korean Wave, Hedonic Lifestyle, and Brand Image on Purchase Decisions of Samsung products in DKI Jakarta, with Customer Relationship Management (CRM) as a moderating variable. Using a quantitative approach and causal associative research, data were collected from 108 Samsung product consumers in DKI Jakarta. The findings reveal that the Korean Wave and Hedonic Lifestyle do not have a significant impact on Purchase Decisions, while Brand Image significantly influences consumers’ purchasing behavior. Additionally, CRM does not strengthen the impact of the Korean Wave or Hedonic Lifestyle on Purchase Decisions, indicating that CRM strategies implemented by Samsung have not effectively leveraged cultural or lifestyle influences. The study also finds that CRM only has a weak and insignificant moderating effect on the relationship between Brand Image and Purchase Decisions, suggesting that rational factors such as product quality and pricing remain the primary determinants of consumer behavior. These results provide valuable insights for marketers on the effectiveness of cultural trends, lifestyle influences, and CRM strategies in shaping consumer purchase decisions.